Role of Fibroblast Growth Factor 23 (FGF23) and αKlotho in Cancer - Ewendt, Franz; Feger, Martina; Föller, Michael (Frontiers in Cell and Developmental Biology, 2021)
Together with fibroblast growth factor (FGF) 19 and 21, FGF23 is an endocrine member of the family of FGFs. Mainly secreted by bone cells, FGF23 acts as a hormone on the kidney, stimulating phosphate excretion and suppressing formation of 1,25(OH)2D3, active vitamin D. These effects are dependent on transmembrane protein αKlotho which enhances the binding affinity of FGF23 for FGF receptors (FGFR). Locally produced FGF23 in other tissues including liver or heart exerts further paracrine effects without involvement of αKlotho. Soluble Klotho (sKL) is an endocrine factor that is cleaved off of transmembrane Klotho or generated by alternative splicing and regulates membrane channels, transporters, as well as intracellular signaling including IGF-1 and WNT pathways, signaling cascades highly relevant for tumor progression. In mice, lack of FGF23 or αKlotho results in derangement of phosphate metabolism and a syndrome of rapid aging with abnormalities affecting most organs and a very short life span. Conversely, overexpression of anti-aging factor αKlotho results in a profound elongation of life span. Accumulating evidence suggests a major role of αKlotho as a tumor suppressor, at least in part by inhibiting IGF-1 and Wnt/β-catenin signaling. Hence, in many malignancies, higher αKlotho expression or activity is associated with a more favorable outcome. Moreover, also FGF23 and phosphate have been revealed to be a factor relevant in cancer. FGF23 is particularly significant for those forms of cancer primarily affecting bone (e.g. multiple myeloma) or characterized by bone metastasis. This review summarizes the current knowledge of the significance of FGF23 and αKlotho for tumor cell signaling, biology, and clinically relevant parameters in different forms of cancer.